Development of nanocrystalline ZnO-SnO2 composite based platform for gas sensing applications - Sahu P.K.; Chandra L.; Prakash R.; Mishra V.N. (My University, 2025)
Nanocrystalline ZnO-SnO2 composite is synthesized incorporating xerogel route. The obtained xerogel undergoes calcination process at a higher temperature (600°C). X-ray diffraction characterization confirms the nanocrystalline growth of composite material. The average crystalline size obtained for ZnO and SnO2 composite metal oxides are 24 nm and 8.9 nm respectively. As obtained nanocrystalline composite powder is further used to fabricate the chemo resistor based gas sensor using simple fabrication techniques; where the active material is grown using brush coating over the pre-patterned gold electrodes. The fabricated chemo resistor based gas sensor is exquisitely sensitive and selective to Acetone rather than other test gases. Acetone having 1000 ppm concentration shows the maximum sensitivity of 84.60%, which is also cross sensitive with other reducing gases such as NH3, CH4, LPG, etc. © 2016 IEEE.